(untitled) (MAUSAM, 1959)
The debriefing reports for 1954-56 received from Dakota aircraft in respect of ice accretion on Assam air routes have been studied in conjunction with synoptic charts and aerological data. A study of the freezing level on these routes, which is intimately connected with icing conditions has also been made.